Embracing Change: The Transition of the West Kazakhstan Medical Journal to English - Tamadon, Amin; A. Kaliyev, Asset; M. Mussin, Nadiar (West Kazakhstan Medical Journal, 2023)
For nearly two decades, the West Kazakhstan Medical Journal (WKMJ) has been a cornerstone of medical knowledge and research in the West Kazakhstan region, serving as a vital platform for local and regional healthcare communities. In a strategic move, the journal is transitioning to the English language, aligning itself with the global discourse in medical science. This transition aims to enhance accessibility, visibility, and impact, fostering international collaborations and contributing valuable insights to the broader medical community. The metamorphosis signifies a commitment to global integration without compromising the journal’s unwavering commitment to quality, ethical publishing, and rigorous peer review. The transformation invites researchers, practitioners, and institutions worldwide to participate in this journey, elevating the exchange of medical knowledge on a global scale